Combined use of Bacillus subtilis strain B‐001 and bactericide for the control of tomato bacterial wilt. Issue 6 (19th December 2016) - Peng, Di; Luo, Kun; Jiang, Huidan; Deng, Yanan; Bai, Lianyang; Zhou, Xiaomao
Abstract: BACKGROUND: Tomato bacterial wilt caused by Ralstonia solanacearum poses a serious threat to tomato production. However, no effective control measures are available. In this study, the bactericide Saisentong was combined with an effective biological control agent, Bacillus subtilis B‐001, to control tomato bacterial wilt under greenhouse and field conditions. RESULTS: Growth of B‐001 in vitro was unaffected by Saisentong. In greenhouse experiments, the combined application of B‐001 and Saisentong via root irrigation or spray resulted in better disease control compared with either agent alone. In two field trials, at a Saisentong concentration of 400 or 500 mg kg −1, the combined treatment was more effective than expected and showed a synergistic effect. A lower concentration of Saisentong (200 or 300 mg kg −1 ) in combination with B‐001 resulted in an antagonistic effect. However, disease control was significantly greater compared with either treatment alone. CONCLUSION: The combination of Saisentong and B‐001 effectively controls tomato bacterial wilt. The integrated strategy represents a promising new tool to control this disease. © 2016 Society of Chemical Industry